Faktor – Faktor yang Mempengaruhi Organizational Citizenship Behaviour Pada Karyawan Mandiri University Group - Priatna, Shafira Fayza; Emilisa, Netania; Khairana, Syifa (Solusi, 2024)
The increasingly intense competition in the era of globalization demands companies continuously adjust their strategies to adapt to changing conditions. Human resources are key to the successful implementation of company activities, requiring a focus on improving their quality. One important factor influencing employee performance is organizational citizenship behaviors (OCB), which are affected by job satisfaction, effective leadership, and workplace spirituality. This study examines the influence of job satisfaction on effective leadership, workplace spirituality, and organizational citizenship behaviors in the Mandiri University Group in the DKI Jakarta Province, as well as the mediating roles of effective leadership and workplace spirituality. This research employs a quantitative approach with data collected through questionnaires from 220 respondents. Data analysis was conducted using Structural Equation Modeling (SEM) and hypothesis testing. The results show that job satisfaction has a significant positive effect on effective leadership and workplace spirituality but not on organizational citizenship behaviors. Workplace spirituality has a significant positive effect on organizational citizenship behaviors, while effective leadership does not. Job satisfaction influences organizational citizenship behaviors through workplace spirituality but not through effective leadership. The implications of this study highlight the importance of enhancing job satisfaction and workplace spirituality to promote organizational citizenship behaviors. Managers and leaders at Mandiri University Group in DKI Jakarta Province should pay more attention to aspects that can improve job satisfaction and workplace spirituality to achieve organizational goals effectively. This study provides theoretical and practical contributions to the development of a model of organizational citizenship behaviors through job satisfaction and workplace spirituality